Dynamical mass generation in QED(3): A non-perturbative approach - Gracia, G. B. de [UNESP]; Pimentel, B. M. [UNESP]; Rabanal, L. [UNESP] (Oxford Univ Press Inc, 2019)
In this work we provide a non-perturbative description of the phenomenon of dynamical mass generation in the case of quantum electrodynamics in 2 + 1 dimensions. We will use the Kugo-Ojima- Nakanishi formalism to conclude that the physical Hilbert space of the asymptotic photon field is the same as that of the Maxwell-Chern-Simons.